Evaluation of Serum Thyrotropin and Urinary Protein level among Pre-eclamptic Pregnancies (Bangladesh Journal of Nuclear Medicine, 2018)
Objective: This study was done to evaluate serum thyrotropin (thyroid stimulating hormone,TSH) and urinary protein level among preeclamptic pregnancies.Patients and methods: This study was conducted at the Institute of Nuclear medicine and Allied Sciences, Rajshahi along with Department of Gynecology & Obstetrics, Rajshahi Medical College Hospital, Rajshahi during the period between 1st July, 2011 and 31st June, 2013.Total 66 preeclamptic pregnant patients who were referred for the assay of serum thyrotropin hormone level were included as sample under the basis of non-random purposive sampling technique. Their age, urinary protein level and level of serum thyrotropin hormone were recorded and analyzed.Results: Among the total enrolled preeclamptic pregnant patients (n=66), Mean (± SD) age was 27 ± 3.88 years (range=19 to 35 years). Regarding urinary protein level, 26 (39.39 %) patients had 1+ urinary protein level and 40 (60.61%) patients had ≥ 2+ urinary protein level. Serum thyrotropin level was 6.16 ± 0.85 (mean ± SD) among total 66 patients. Among the preeclamptic pregnant patients having 1+ urinary protein level,  thyrotropin level was 5.38 ± 0.70 (mean ± SD) and 6.67 ± 0.49 (mean ± SD) among the patients having  ≥ 2+ urinary protein level.Conclusion: Thyrotropin level is higher in preeclamptic pregnant patients and reflects severity of preeclampsia.Bangladesh J. Nuclear Med. 19(2): 120-122, July 2016